Paraoxonase 1 gene polymorphisms in lipid oxidation and atherosclerosis development - Vavlukis, Marija; Vavlukis, Ana; Krsteva, Katerina; Topuzovska, Sonja (Frontiers in Genetics, 2022)
Paraoxonase 1 (PON1) is calcium-dependent aryldialkylphosphatase, thought to possess anti-oxidant, anti-adhesion, anti-inflammatory, anti-thrombosis, and anti-apoptosis effects, as well as lipid-modifying properties. Numerous clinical studies have shown associations between different PON1 polymorphisms and different cardiovascular pathologies. The rs622 (c.575A>G) and the rs854560 (c.163A>T) is the most studied PON1 SNPs in the coding region, with rs705381 (− 162A/G), rs854572 (− 909G/C), and rs705379 (− 108C/T) being the most studied SNPs in the regulatory PON1 gene region. The three major PON1 activities are aryldialkylphosphatase, arylesterase, and lactonase activity. The different SNPs affect PON1 serum concentrations and enzyme activity, thus leading to pro-/anti-atherogenic effects. In that setting, it is very difficult to establish whether the genotype or phenotype of PON1 is primarily associated with cardiovascular risk. Given the current scientific evidence, PON1 genotyping might be reasonable in patients with high and very high cardiovascular risk.